ATiPreTA: An analytical model for time-dependent prediction of terrorist attacks - Kebir, Oussama; Nouaouri, Issam; Rejeb, Lilia; Ben Said, Lamjed (Zielona Góra: Uniwersytet Zielonogórski)
In counter-terrorism actions, commanders are confronted with difficult and important challenges. Their decision-making processes follow military instructions and must consider the humanitarian aspect of the mission. In this paper, we aim to respond to the question: "What would the casualties be if governmental forces reacted in a given way with given resources?" Within a similar context, decision-support systems are required due to the variety and complexity of modern attacks as well as the enormous quantity of information that must be treated in real time.
Keywords: terrorist attacks; attack classification; mathematical modeling; dynamic behavior simulation; damage prediction